2019
DOI: 10.4103/jcvjs.jcvjs_8_19
|View full text |Cite
|
Sign up to set email alerts
|

Is cast an option in the treatment of thoracolumbar vertebral fractures?

Abstract: Background: Thoracolumbar vertebral fractures are common in high-energy trauma and often are associated to other concomitant injuries. Currently, brace and Closed Reduction and Casting (CRC) are the two conservative treatments proposed by literature. Despite CRC was widely used in the past, today brace is preferred. The aim of our study is to evaluate clinical and radiographic outcomes of thoracolumbar type A fractures, not associated with other injuries, treated with CRC. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Complications were extremely rare in both arms of the study with the same rate of other studies that show how the posterior approach is safer for the patient. [24252627282930] Clinical results were also satisfactory [Figures 1 and 2]. The scores obtained with the administration of the SRS 24 questionnaire (which has been used for years in studies published in the literature)[3132] were comparable in the two study-arms.…”
Section: Discussionmentioning
confidence: 76%
“…Complications were extremely rare in both arms of the study with the same rate of other studies that show how the posterior approach is safer for the patient. [24252627282930] Clinical results were also satisfactory [Figures 1 and 2]. The scores obtained with the administration of the SRS 24 questionnaire (which has been used for years in studies published in the literature)[3132] were comparable in the two study-arms.…”
Section: Discussionmentioning
confidence: 76%
“…Thanks to the good results, we reported that, in this study, associated with other reported in literature, we can suggest surgeons to consider the surgical approach with PMMA CSF to osteoporosis fracture as a safe and reliable treatment. Despite these results is suggestable, for very frail patients, to consider conservative approaches,[ 22 ] and every surgeon that decides to approach this kind of surgery must be aware of the many possible complications; it is strongly recommended to avoid the occasional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A possible alternative treatment is the use of cast on traction bed to reduce and contain TL vertebral fracture; however, a great dislocation of the posterior wall is a contraindication. [ 11 ] On the other hand, surgical stabilization of unstable burst fracture with or without poly methyl methacrylate augmentation could be a valuable choice and suitable to different age of patients according to bone mineral density. [ 12 13 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%